20th Anniversary Conference of the Journal of Advances in Educational Supervision. Conclusions from Discussion Panel 3: Internal Organization of the Educational Inspectorate and the Planning of Its Actions - Úbeda-Portugués Ávila, Gema; Rodríguez Bravo, Marcos; Moreno López, Rubén (Avances en Supervisión Educativa, 2026)
This article highlights the conclusions extracted in a discussion panel about the Educational Inspectorate's internal organization and action-planning processes within the framework of the 20th Anniversary Conference of the Journal of Advances in Educational Supervision. Gema Úbeda-Portugués Ávila submitted the screening of multiple articles about these issues. Therefore, the first part includes a summary of the main keywords to create a dialogue space before the discussion. The last part collects the conclusions of the deliberation about three important topics for us: specialization versus generalization; inspection plans and double dependency, and collective actions. Definitely, this article provides insights into how to meet the demands of our education system.
Keywords: educational inspectorate; organization and management; planning; experts; dependence; cooperation